Caveolin-1 reduces HIV-1 infectivity by restoration of HIV Nef mediated impairment of cholesterol efflux by apoA-I - Lin, Shanshan (BioMed Central, 2012)
BACKGROUND: HIV infection results in inhibited cholesterol efflux by apolipoprotein A-I (apoA-I) in macrophages, and this impairment involves Nef mediated down-regulation and redistribution of ATP-binding cassette transporter A1 (ABCA-1). We investigated the effect of caveolin-1 (Cav-1) on the cholesterol efflux by apoA-I in HIV infected primary and THP-1 cell-differentiated macrophages as well as astrocyte derived glioblastoma U87 cells. RESULTS: Our results reveal that Cav-1 restores the Nef -mediated impairment of cholesterol efflux by apoA-I in both cell types. Co-immunoprecipitation studies indicate a physical association of Cav-1 and Nef. The level of ABCA-1 expression remains the same whether Cav-1 is over-expressed or not. In addition, we examined the cholesterol composition of HIV particles released from Cav-1 treated cells and identified that the cholesterol content is dramatically reduced. The infectivity level of these virus particles is also significantly decreased. CONCLUSIONS: These observations suggest that the interplay of Cav-1 with Nef and cholesterol subsequently counters Nef induced impairment of cholesterol efflux by apoA-l. The findings provide a cellular mechanism by which Cav-1 has an ability to restore HIV mediated impairment of cholesterol efflux in macrophages. This subsequently influences the cholesterol content incorporated into virus particles thereby inhibiting HIV infectivity and contributing to HIV’s persistent infection of macrophages.